Two-Electron Reaction without Structural Phase Transition in Nanoporous Cathode Material. (28th May 2012) - Matsuda, Tomoyuki; Moritomo, Yutaka
Abstract : We investigated the charge/discharge properties, valence states, and structural properties of a nanoporous cathode material Li x Mn [ Fe ( CN ) 6 ] 0.83 · 3.5 H 2 O . The film-type electrode of Li x Mn [ Fe ( CN ) 6 ] 0.83 · 3.5 H 2 O exhibited a high charge capacity ( = 128 mAh g - 1 ) and a good cyclability (87% of the initial value after 100 cycles) and is one of the promising candidates for Li-ion battery cathode. X-ray absorption spectra near the Fe and Mn K-edges revealed that the charge/discharge process is a two-electron reaction; that is, Mn II –NC–Fe II, Mn II –NC–Fe III, and Mn III –NC–Fe III . We further found that the crystal structure remains cubic throughout the charge/discharge process. The lattice constant slightly increased during the [ Fe II ( CN ) 6 ] 4 - / [ Fe III ( CN ) 6 ] 3 - oxidization reaction while decreased during the Mn II / Mn III oxidization reaction. The two-electron reaction without structural phase transition is responsible for the high charge capacity and the good cyclability.